Potensi Pemanfaatan Tenaga Surya Menggunakan Fotovoltaik di Kawasan Tana Mori, Labuan Bajo - Anindito Nurprabowo; Dani Rusirawan (Universitas Islam Raden Rahmat, Malang, 2024)
The potential of solar energy in Indonesia is very large, which is approximately 4.8 KWh/m2, but unfortunately the utilization still low even though the limitations of fossil resources are increasingly worrying. In line with this, the Tana Mori area which is proclaimed to be the location of the G20 Summit must prioritize environmentally friendly concepts, one of which is using renewable energy in the form of utilizing sunlight as an alternative source of electrical energy. To find out the potential of this solar power plant, the Homer Pro application is used, where this application can simulate a renewable energy system with initial input, namely the need for electrical power to be used and draw up a schematic of the technology components that will be applied to this location. With a power requirement of 392.74 kW for the utility system, one photovoltaic system with a capacity of 500 kWp can be used, where the simulation results also produce procurement costs that are almost comparable to the costs for operating and maintaining the system if not using photovoltaic.